The incentive effects of minimum pensions - Sergi Jiménez-Martín (IZA World of Labor, 2014)
The main purpose of minimum pension benefit programs and old-age social assistance programs is to guarantee a minimum standard of living after retirement and thus to alleviate poverty in old age. In many developing and developed countries, the minimum pension program is a key welfare program and a major influence on the retirement decisions of low-income workers and workers with erratic work histories. The design of many minimum pension programs tends to create strong incentives for low-income workers to retire as soon as they become eligible for the program, which is often earlier than the normal retirement age.
Keywords: H55; H75; J22; J26; D91; 330; retirement; incentives to retire; life-cycle model; minimum pension